2010
DOI: 10.1017/s0025315410001700
|View full text |Cite
|
Sign up to set email alerts
|

Environmental variables influencing the Callinectes (Crustacea: Brachyura: Portunidae) species distribution in a tropical estuary—Cachoeira River (Bahia, Brazil)

Abstract: The genus Callinectes comprises seven species of blue crab found on the Brazilian coast, almost all are recorded in Cachoeira River estuary. The objective of this study is to analyse distribution of Callinectes species in the estuary of Cachoeira River (Ilhéus, Bahia). Monthly collections were conducted in the low tide of neap tide for a year and in five stations distributed according to the estuary salinity gradient. Six traps were assembled and submerged at each station for two hours. Sediment samples were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 18 publications
0
11
0
3
Order By: Relevance
“…However, Buchanan & Stoner (1988) suggested that the distribution pattern of Callinectes species is also the result of complex intra-or interspecific interactions among other congener species. Fransozo et al (1992), McClintock et al (1993), Negreiros-Fransozo & Fransozo (1995 and Carvalho & Couto (2011) studied biological aspects related to the distribution, abundance, habitat and migration of Callinectes species on the Atlantic coast, and verified that the juveniles of the majority of the species inhabit estuaries, whereas mature females conserve energy in low-salinity environments to spawn before subsequently migrating with a welldeveloped egg mass to more saline waters, offshore, where the larvae hatch.…”
Section: Introductionmentioning
confidence: 98%
“…However, Buchanan & Stoner (1988) suggested that the distribution pattern of Callinectes species is also the result of complex intra-or interspecific interactions among other congener species. Fransozo et al (1992), McClintock et al (1993), Negreiros-Fransozo & Fransozo (1995 and Carvalho & Couto (2011) studied biological aspects related to the distribution, abundance, habitat and migration of Callinectes species on the Atlantic coast, and verified that the juveniles of the majority of the species inhabit estuaries, whereas mature females conserve energy in low-salinity environments to spawn before subsequently migrating with a welldeveloped egg mass to more saline waters, offshore, where the larvae hatch.…”
Section: Introductionmentioning
confidence: 98%
“…Callinectes ornatus ocorre desde a Carolina do Norte (EUA) até o Rio Grande do Sul (Brasil), em fundos de areia, lama ou conchas, em áreas estuarinas com maior salinidade, do entre-marés até 75 m de profundidade (Melo, 1996;Carvalho & Couto, 2011).…”
Section: Introductionunclassified
“…found that A. cribrarius presented a lower prevalence of infestation by O. lowei and other epibionts during winter. Since the relative contribution of each demographic category (males, non-ovigerous females, ovigerous females and juveniles) to the population of a crab species often varies temporally (Santos et al, 1995;Johnson and Perry, 1999;Carvalho and Couto, 2011;Andrade et al, 2013), these categories might have been represented differently in our sample when compared to those of previous studies, which may explain some divergences in results (e.g. infestation on ovigerous females tend to be higher than non-ovigerous females and males, probably because these females has longer intermolt periods; Costa et al, 2010).…”
Section: Epibiosis In Portunid Crabsmentioning
confidence: 99%